Flexural impact response of textile-reinforced aerated concrete sandwich panels. (5th December 2015) - Dey, V.; Zani, G.; Colombo, M.; Di Prisco, M.; Mobasher, B.
Abstract: Mechanical response of textile-reinforced aerated concrete sandwich panels was investigated using an instrumented three-point bending experiment under static and low-velocity dynamic loading. Two types of aerated concrete: autoclaved aerated concrete (AAC) and polymeric Fiber-Reinforced Aerated Concrete (FRAC) were used as the core material. Skin layer consisted of two layers of Alkali Resistant Glass (ARG) textiles and a cementitious binder. Performance of ductile skin-brittle core (TRC–AAC) and ductile skin-ductile core (TRC–FRAC) composites was evaluated in terms of flexural stiffness, strength, and energy absorption capacity. The effect of impact energy on the mechanical properties was measured at various drop heights on two different cross-sections using energy levels up to 40 J and intermediate strain rates up to 20 s − 1 . The externally bonded textile layers significantly improved the mechanical properties of light-weight low-strength aerated concrete core under both loading modes. Dynamic flexural strength was greater than the static flexural strength by as much as 4 times. For specimens with larger cross-sections, unreinforced-autoclaved AAC core had a 15% higher apparent flexural capacity. With 0.5% volume of polypropylene fibers in the core, the flexural toughness however increased by 25%. Cracking mechanisms were studied using high speed image acquisition and digital image correlation (DIC) technique. Graphical abstract: Highlights: Sandwich composite with glass textile reinforced cementitious skin and aerated concrete core was successfully developed Enhancement in static flexural strength by 200–400%, and toughness by 300-600% due to the textile reinforced skin layer Mechanical properties under impact loading at strain rates between 0.01-3 s -1 are 2-4 times greater than static properties